Review of the genus Leptocysta Stål with descriptions of two new species (Hemiptera: Heteroptera: Tingidae) from Argentina - Montemayor Borsinger, Sara Itzel (2010)
Two new species of Leptocysta are described from Argentina, L. dellapei n. sp. and L. delrioae n. sp. An updated key to species is provided together with illustrations of the diagnostic characters, habitus photographs and new distributional records for Argentina.